2019
DOI: 10.3846/jbem.2019.9659
|View full text |Cite
|
Sign up to set email alerts
|

Sectoral Analysis of the Effectiveness of Bank Risk Capital in the Visegrad Group Countries

Abstract: Bank risk capital (capital at risk) is identified with the value of banks’ own funds maintaining to absorb potential losses and protect against insolvency. It is calculated for the capital adequacy ratios, recommended by the Basel Committee on Banking Supervision. On other words, it is a kind of banks’ capital that financing securing the negative effects of risk occurring. A comparative analysis of effectiveness of bank risk capital in the Visegrad Group countries, constituting the main objective of the study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 51 publications
(106 reference statements)
1
69
0
Order By: Relevance
“…The only way to sustainable development and gaining a competitive advantage in the market is to employ and support people who can work, use and develop their knowledge potential and have a sustainable relationship with the environment in which they work. The results of the study by [36] confirm the interaction between ecological behavior of employees and corporate environmental performance. Gaining a relatively stable and strategic position of the enterprise in the global market requires fundamental changes in the thinking of managers and HRM.…”
Section: Theoretical Backgroundsupporting
confidence: 60%
“…The only way to sustainable development and gaining a competitive advantage in the market is to employ and support people who can work, use and develop their knowledge potential and have a sustainable relationship with the environment in which they work. The results of the study by [36] confirm the interaction between ecological behavior of employees and corporate environmental performance. Gaining a relatively stable and strategic position of the enterprise in the global market requires fundamental changes in the thinking of managers and HRM.…”
Section: Theoretical Backgroundsupporting
confidence: 60%
“…Studies have found that green HRM affects the psychological green climate of employees, which affects the performance of EGB (Dumont et al, 2016;Saeed et al, 2019). Other studies have shown that green HRM practices in the organizations activated the commitment toward environmental sustainability, which leads to EGB (Pham et al, 2019). However, to better understand the underlying factors in which green HRM affects EGB, more studies are still encouraged (Ren et al, 2018).…”
Section: Need For the Studymentioning
confidence: 99%
“…In the test for moderated mediating effect and following the recommendations of Edwards and Lambert (2007) and Pham, Tuckova, and Pham (2019), this study used the PRO-CESS macro for SPSS with 5,000 bootstrap samples at the 0.05 level to test H5 (Table 6). The results indicated that at high levels of information security awareness (i.e., mean + 1 SD), positive emotions had a considerable impact on protection-motivated behaviours through self-efficacy (β = 0.325, p < 0.001).…”
Section: End Ofmentioning
confidence: 99%